2007
DOI: 10.1002/mrdd.20166
|View full text |Cite
|
Sign up to set email alerts
|

Education and children with Down syndrome: Neuroscience, development, and intervention

Abstract: Of the recent advances in education-related research in Down syndrome, the characterization of the Down syndrome behavioral phenotype has become a potentially critical tool for shaping education and intervention in this population. This article briefly reviews the literature on brain-behavior connections in Down syndrome and identifies aspects of the Down syndrome behavioral phenotype that are potentially relevant to educators. Potential challenges to etiologically informed educational planning are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 110 publications
1
96
0
8
Order By: Relevance
“…Regarding the educational process, social inclusion is constantly changing, and needs to be expanded through effective strategies. This is mostly seen in building capacity and interaction between people, and it depends on language and body-mind exploration [6]. All of these aspects contributed to the educational, emotional and social adjustments in DS through the process of dance learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the educational process, social inclusion is constantly changing, and needs to be expanded through effective strategies. This is mostly seen in building capacity and interaction between people, and it depends on language and body-mind exploration [6]. All of these aspects contributed to the educational, emotional and social adjustments in DS through the process of dance learning.…”
Section: Resultsmentioning
confidence: 99%
“…Gilmore, Campbell and Cuskelly [5] and Fidler and Nadel [6] highlight collaborative education to enable learning in people with disabilities, including DS.…”
Section: Introductionmentioning
confidence: 99%
“…Mother's learning of having a baby with DS diagnosis is established by clinical observations immediately after birth and diagnosed by genetic tests, as can be diagnosed by screening and testing during pregnancy (Contestabile, Benfenati, & Gasparini, 2010). The studies conducted with the families and especially mothers who have infants with deficiencies reveal that open and clear diagnosis has provided psychosocial advantages in favor of the mothers (Abbeduto, Warren, & Conners, 2007;Cocchi, Gualdi, Bower, Halliday, Jonsson, Myrelid, & Annere, 2010;Contestabile, Benfenati, & Gasparini, 2010;Fidler & Nadel, 2007;Freeman & Kasari, 2002). Findings showed that well-known and early genetics diagnosis, such as DS, cause children's mothers to reach their social support groups more quickly and have emotional comfort in permanent and significant dimensions.…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%
“…Thus, children with Down syndrome have deficits in language area, verbal short-term memory and executive functions (Fidler, 2005, Vicari et al, 2004. The areas in which children with Down syndrome reportedly have relative strengths are visual perception and visual motor skills (Fidler & Nadel, 2007). Besides visual perception, these relative strengths also involve implicit memory, which in turn can, together with visual perception, affect the reading skills, especially word identification.…”
Section: Introductionmentioning
confidence: 99%